The effect of a transaction tax on exchange rate volatility - Markku Lanne; Timo Vesala (Bank of Finland, 2006)
We argue that a transaction tax is likely to amplify, not dampen, volatility in the foreign exchange markets.Our argument stems from the decentralised trading practice and the presumable discrepancy between informed and uninformed traders valuations.Since informed traders valuations are likely to be less dispersed, a transaction tax penalises informed trades disproportionately, leading to increased volatility.Empirical support for this prediction is found by investigating the effect of transaction costs on the volatility of DEM/USD and JPY/USD returns. High-frequency data are used and an increase in transaction costs is found to have a significant positive effect on volatility.
URN:NBN:fi:bof-20140807244
Keywords: F31; F42; G15; G28; 330; transaction tax; exchange rates; volatility